Inisiasi Pengembangan Pemasaran Ikan Teri (Stolephorus Spp.) dan Pembentukan Kelembagaan dalam Rangka Pemberdayaan Masyarakat di Desa Saramaake, Halmahera Timur - Ujang Sehabudin; Faleh Setia Budi; Dian Herawati; Joko Purnomo; . Sulistiono (Institut Pertanian Bogor, 2017)
One of the villages in East Halmahera which has been known as anchovy production area is Saramaake Village. Commonly, a community in this village has an income from the anchovy fishery. The product of the anchovy fish is high and various in size, while fish marketing increase and good institution did not establish yet. This activity has been done for 7 months from June 2016January 2017, aimed to improve the product marketing, and institution establishment through training and mentoring. According to the activity has been done, marketing of the dried anchovy which was marketed previously in big size (bulky), it can be marketed in small size with better packaging (100, 200, 500, and 1.000 g) and labelling, while the processed fish can be marketed also in packaging (100 g) and labelling. The institution has been established a namely cooperative small business group (KUB) both for fisherman and fish processing person. Through the marketing development and institution establishment, fishermen can manage their fish product better.